Social Innovation at Technical Universities – State of the Art - Berg, Julia; Leicht-Scholten, Carmen (Proceedings of ISPIM Conferences, 2021)
This paper presents the state of the art in promoting social innovation at five leading technical universities in Europe. We assess how these leading technical universities implement social innovation in their strategies, teaching, and research. The results show that all universities highlight the importance of finding solutions to global challenges and addressing Responsible Research and Innovation (RRI) as a fundamental university strategy for example by promoting social innovation. Moreover, all address the universities’ need to contribute to sustainability and the Sustainable Development Goals. However, social innovation does not play an important role in research and teaching as the results show that social innovation has so far been little addressed in research and teaching. Based on the political framework in the five European countries, we draw up conclusions for technical universities
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités

Social Innovation at Technical Universities – State of the Art - Berg, Julia; Leicht-Scholten, Carmen (Proceedings of ISPIM Conferences, 2021)
This paper presents the state of the art in promoting social innovation at five leading technical universities in Europe. We assess how these leading technical universities implement social innovation in their strategies, teaching, and research. The results show that all universities highlight the importance of finding solutions to global challenges and addressing Responsible Research and Innovation (RRI) as a fundamental university strategy for example by promoting social innovation. Moreover, all address the universities’ need to contribute to sustainability and the Sustainable Development Goals. However, social innovation does not play an important role in research and teaching as the results show that social innovation has so far been little addressed in research and teaching. Based on the political framework in the five European countries, we draw up conclusions for technical universities
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités